Ultrafast 2D-IR spectroscopy of [NiFe] hydrogenase from E. coli reveals the role of the protein scaffold in controlling the active site environment. Issue 40 (6th October 2022) - Wrathall, Solomon L. D.; Procacci, Barbara; Horch, Marius; Saxton, Emily; Furlan, Chris; Walton, Julia; Rippers, Yvonne; Blaza, James N.; Greetham, Gregory M.; Towrie, Michael; Parker, Anthony W.; Lynam, Jason; et al.
Abstract : Ultrafast two-dimensional infrared (2D-IR) spectroscopy of Escherichia coli Hyd-1 ( Ec Hyd-1) reveals the structural and dynamic influence of the protein scaffold on the Fe(CO)(CN)2 unit of the active site. Abstract : Ultrafast two-dimensional infrared (2D-IR) spectroscopy of Escherichia coli Hyd-1 ( Ec Hyd-1) reveals the structural and dynamic influence of the protein scaffold on the Fe(CO)(CN)2 unit of the active site. Measurements on as-isolated Ec Hyd-1 probed a mixture of active site states including two, which we assign to Nir -SI/II, that have not been previously observed in the E. coli enzyme. Explicit assignment of carbonyl (CO) and cyanide (CN) stretching bands to each state is enabled by 2D-IR. Energies of vibrational levels up to and including two-quantum vibrationally excited states of the CO and CN modes have been determined along with the associated vibrational relaxation dynamics. The carbonyl stretching mode potential is well described by a Morse function and couples weakly to the cyanide stretching vibrations. In contrast, the two CN stretching modes exhibit extremely strong coupling, leading to the observation of formally forbidden vibrational transitions in the 2D-IR spectra. We show that the vibrational relaxation times and structural dynamics of the CO and CN ligand stretching modes of the enzyme active site differ markedly from those of a model compound K[CpFe(CO)(CN)2 ] in aqueous solution and conclude that the protein scaffold creates a unique biomolecular environment for the NiFe site that cannot be represented by analogy to simple models of solvation.